São Paulo 9 : United States of America : Edward Hopper - Environment U.S.A. : 1957-1967/Meio-Natural U.S.A. : 1957-1967. - Goodrich, Lloyd; Ripley, Dillon; Scott, David W.; Bienal de São Paulo, 1967 (Washington : Smithsonian Institution, 1967)
D'Arcangelo, Allan ; Foulkes, Llyn ; Gill, James ; Graziani, Sante ; Harris, Paul ; Hopper, Edward ; Indiana, Robert ; Johns, Jasper ; Laing, Gerald ; Lichtenstein, Roy ; Lindner, Richard ; Morley, Malcolm ; Nesbitt, Lowell ; Oldenburg, Claes ; Raffaele, Joe ; Rauschenberg, Robert ; Rosenquist, James ; Ruscha, Edward ; Segal, George ; Thiebaud, Wayne ; Warhol, Andy ; Wesselmann, Tom
biog. [10 p.]
Engels & Portugees
IX Bienal de São Paulo United States of America, MAM (Museu de Arte Moderna de São Paulo), São Paulo, September 22, 1967 - 8 de janeiro 1968
boek
Keywords: U.S.A.